Green Growth : Towards a Strategy for Uruguay - World Bank Group (World Bank, Washington, DC, 2018)
Green growth aims to reconcile economic growth and environmental sustainability, marrying environmental objectives to productivity objectives, job creation, adoption of technology and greater added value. In Uruguay, natural capital plays a central role in promoting its export-oriented growth model. Although the country has already been involved in a sustainable growth trajectory for key economic sectors (such as agriculture, tourism, forest management, energy), Uruguay needs to define a green growth strategy to face the emerging environmental challenges, and to meet its goals of production and international commitments targets in a sustainable way.In this context, this report provides a roadmap to promote green growth in Uruguay, with the objective of promoting growth and, at the same time, preserving the asset base on which this growth depends. The work developed is based on the findings of the Technical Assistance Green Growth in Uruguay financed by the World Bank that took place between August 2016 and March 2018, as well as Uruguay's experience in environmental sustainability policies, the collection of international evidence, and World Bank's experience with Uruguay during the last decade.This report proposes an operational definition for Uruguay, presents an analysis of the achievements made so far in the country in the environmental-productive field, and examines future challenges for which a green growth approach could be important. Soil erosion, water pollution from nutrients, pesticide management, and greenhouse gas emissions represent some of the recurring themes in the country's decision-making. In addition, the management of water quality and water quantity variability represent particularly important challenges, both for production and for the availability of water suitable for domestic consumption.Lastly, this work includes recommendations to generate a green growth strategy in Uruguay. For this purpose, a five-step roadmap is proposed to promote green growth and to advance on its strategic goals. These steps are: identify green growth policies to boost the country's growth, identify the environmental benefits of these policies, establish criteria to prioritize potential policies of green growth, design green growth policy instruments, and establish the mechanism to evaluate and adjust green growth policies. This roadmap is complemented with recommendations on the institutional framework needed to support the sustainability of a green growth vision.This report is part of a series of five complementary analytical products generated under the World Bank's Green Growth Technical Assistance in Uruguay.